Pemberdayaan Pedagang Kuliner Melalui Pelatihan Kewirausahaan Dikelurahan Bojong Rawa Lumbu Kota Bekasi - Achmad Jaelani; Hastuti Indra Sari; Mulyadi; Rachmad Risqy K; Atik Budi P; Dewi Pertiwi; Arsid (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Community service represents a concrete initiative aimed at enhancing the well-being and competitiveness of collaborating partners. The rationale behind this community service initiative is to address challenges confronted by culinary traders, encompassing aspects such as business management, marketing, financial administration, and product development. The execution of community service endeavors is centered on empowering culinary traders in RW 026 Bojong Rawa Lumbu Village, Bekasi City, through entrepreneurship training facilitated by the Faculty, Staff, and Students of the Institute of Business and Communication Swadaya. The primary objective of this community service is to bolster the capacity of culinary traders in effectively managing their enterprises and fostering a positive influence on local economic development. The methodology employed in this community service entails training sessions and practical entrepreneurship exercises tailored for partner culinary traders. The outcomes of this service manifest in heightened sales turnover, contributing positively to both local economic development and the well-being of the culinary traders involved.